Crosslink network evolution of BIIR/EPDM blends during peroxide vulcanization. (May 2017) - Wang, Jinyuan; Pan, Sanshui; Zhang, Yong; Guo, Sharon
Abstract: Crosslink network evolution of brominated butyl rubber (BIIR)/ethylene–propylene–diene-monomer rubber (EPDM) blends during peroxide vulcanization is studied at a meso-scale level. In this work, EPDM is added as a co-agent to increase the crosslink density of BIIR vulcanization. With increasing EPDM content from 0 to 20 phr, the maximum torque of BIIR/EPDM compounds during vulcanization increases by 73%, reaching to 3.40 dNm. Vulcanization kinetic study shows that addition of EPDM favors to the crosslinking of BIIR compound. Meanwhile, the addition of 20 phr EPDM contributes to an increase in the crosslink density of BIIR/EPDM(80/20) vulcanizate, avoiding downward trend at post-cure period in comparison with BIIR only. Crosslink network evolution of BIIR/EPDM blends is divided into three periods during peroxide vulcanization at 150 °C. The role of EPDM in the crosslink network evolution is studied by proton nuclear magnetic resonance, and a "network patching" mechanism is proposed in which EPDM is implied to work as patch on damaged crosslink network resulted from the degradation nature of BIIR.